Brain structural connectome in relation to PRRT2 mutations in paroxysmal kinesigenic dyskinesia. Issue 14 (27th June 2020) - Li, Lei; Lei, Du; Suo, Xueling; Li, Xiuli; Yang, Chen; Yang, Tianhua; Ren, Jiechuan; Chen, Guangxiang; Zhou, Dong; Kemp, Graham J.; Gong, Qiyong
Abstract: This study explored the topological characteristics of brain white matter structural networks in patients with Paroxysmal Kinesigenic Dyskinesia (PKD), and the potential influence of the brain network stability gene PRRT2 on the structural connectome in PKD. Thirty‐five PKD patients with PRRT2 mutations (PKD‐M), 43 PKD patients without PRRT2 mutations (PKD‐N), and 40 demographically‐matched healthy control (HC) subjects underwent diffusion tensor imaging. Graph theory and network‐based statistic (NBS) approaches were performed; the topological properties of the white matter structural connectome were compared across the groups, and their relationships with the clinical variables were assessed. Both disease groups PKD‐M and PKD‐N showed lower local efficiency (implying decreased segregation ability) compared to the HC group; PKD‐M had longer characteristic path length and lower global efficiency (implying decreased integration ability) compared to PKD‐N and HC, independently of the potential effects of medication. Both PKD‐M and PKD‐N had decreased nodal characteristics in the left thalamus and left inferior frontal gyrus, the alterations being more pronounced in PKD‐M patients, who also showed abnormalities in the left fusiform and bilateral middle temporal gyrus. In the connectivity characteristics assessed by NBS, the alterations were more pronounced in the PKD‐M group versus HC than in PKD‐N versus HC. As well as the white matter alterations in the basal ganglia‐thalamo‐cortical circuit related to PKD with or without PRRT2 mutations, findings in the PKD‐M group of weaker small‐worldness and more pronounced regional disturbance show the adverse effects of PRRT2 gene mutations on brain structural connectome. Abstract : This study explored the topological characteristics of brain white matter structural networks in patients with paroxysmal kinesigenic dyskinesia (PKD), and the potential influence of the brain network stability gene PRRT2 on the structural connectome in PKD.